DINAMIKA YURISPRUDENSI SEBAGAI SUMBER HUKUM DALAM SISTEM HUKUM DI INDONESIA - Nahrowi, Nahrowi; Murtadlo, Muhammad Ali (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2024)
This article explores the dynamics of jurisprudence as a source of law within Indonesia's legal system. It highlights the role of jurisprudence in shaping legal decisions and its status among other legal sources such as legislation and customary law. Despite being an essential component, jurisprudence often receives inadequate attention, leading to inconsistencies in its application across various judicial decisions. This paper employs a qualitative research approach, analyzing relevant literature and case law to examine the acceptance and challenges of jurisprudence in Indonesian practice. Through case studies of key court decisions, the article illustrates the influence of jurisprudence on judicial reasoning and legal development. The findings indicate that jurisprudence significantly contributes to the formation of legal norms and provides a crucial framework for legal interpretation. However, challenges such as inconsistent application and limited understanding among judges highlight the need for greater emphasis on jurisprudence in legal education and practice. The article concludes by recommending measures to enhance the quality and consistency of jurisprudence, thereby strengthening its role as a source of law in Indonesia.